Angels or demons? Evidence on the impact of private equity firms on employment - Eva Nathusius; Ann-Kristin Achleitner (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
The impact of private equity firms on employment in their portfolio companies is a controversial topic widely discussed in academia and in practice in recent years. A large body of research has resulted from this debate. The studies are focused on different aspects of employment and are based on a variety of methodologies as well as samples representing e.g. different types of buyouts and geographies. The aim of this paper is to provide access to and enhance the understanding of the highly fragmented literature by way of a systematic review and to discuss areas for future research. We review evidence on employment growth, financial and non-financial indicators of employment in a total of 49 studies. The analysis of similarities and differences of the studies revealed manifold consequences of private equity on employment. Our review reveals that the impact varies across different employment indicators and between geographies. We therefore conclude that it is not possible to label private equity firms either positively or negatively as 'angels or demons' as this would not take account of their complex and heterogeneous effects on employees post-buyout.
Keywords: G24; L26; J63; 330; private equity; employment; industrial relations; entrepreneurial companies; systematic review